Integrated Reporting and Corporate Profitability: Evidence from Manufacturing Firms in South Africa - Rudolph, Makhathini Lungani; Aliamutu, Kansilembo (International Review of Management and Marketing, 2026)
This study explored the relationship between integrated reporting disclosure and corporate profitability among manufacturing firms listed on the Johannesburg stock exchange in south Africa. Integrated reporting promoted under the king III and king IV codes of corporate governance, requires firms to present financial and non-financial information in a single value-oriented framework. The study focuses on three key disclosure dimensions; economic, environmental and social and evaluates their impact on profitability measured by return assets, return on equity and return on sales. A quantitative research design was adopted using secondary data collected from published integrated reports and audited annual financial statements covering the period from 2021 to 2025. The sample was selected through purposive sampling to ensure data consistency. Multiple linear regression analysis was used to test the hypotheses following diagnostic test for normality, multicollinearity, heteroscedasticity and autocorrelation to ensure model robustness. The findings reveal a positive association between integrated reporting disclosure and corporate profitability among manufacturing firms listed on the Johannesburg Stock Exchange. Economic disclosure significantly enhances ROE and ROS, indicating that transparency strengthens investors confidence and operational performance. Environmental disclosure positively influences profitability recommendation that sustainability initiatives improve resource efficiency and risk management, social disclosure demonstrates a positive effect on ROE and ROS, highlighting the importance of stakeholder engagement, use welfare and corporate social responsibility in driving financial results.